A full CIRCLE: inclusion of autistic doctors in the Royal College Of Psychiatrists' values and Equality Action Plan. (July 2022) - McCowan, Sue; Shaw, Sebastian C. K.; Doherty, Mary; Grosjean, Bernadette; Blank, Paula; Kinnear, Malcolm
Summary: Autistic psychiatrists bring strengths and values to the workforce and ask to be acknowledged and supported as part of the Royal College of Psychiatrists' CIRCLE values and Equality Action Plan . Courage and collaboration are required to jointly learn and innovate, promoting well-being, resilience and excellence for autistic doctors.